2009
DOI: 10.5194/bgd-6-8589-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of carbonate ion concentration and irradiance on calcification in foraminifera

Abstract: Abstract. The effect of carbonate ion concentration ([CO32−]) on calcification rates estimated from shell size and weight was investigated in the planktonic foraminifera Orbulina universa and Globigerinoides sacculifer. Experiments on G. sacculifer were conducted under two irradiance levels (35 and 335 μmol photons m−2 s−1). Calcification was ca. 30% lower under low light than under high light, irrespective of the [CO32−]. Both O. universa and G. sacculifer exhibited reduced final shell weight and calcificatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…2,3, Supplementary Material). Environmental differences offer an alternative explanation for variable isotopic patterns among sites, including factors such as the availability of photosynthetically active radiation, temperature, carbonate ion effects, and the extent of water-column stratification (Spero et al 1997; Lombard et al 2009; Henehan et al 2016). This class of explanations is less parsimonious than those invoking changed photosymbiont associations, because variable combinations of environmental changes need to be evoked at each site (Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…2,3, Supplementary Material). Environmental differences offer an alternative explanation for variable isotopic patterns among sites, including factors such as the availability of photosynthetically active radiation, temperature, carbonate ion effects, and the extent of water-column stratification (Spero et al 1997; Lombard et al 2009; Henehan et al 2016). This class of explanations is less parsimonious than those invoking changed photosymbiont associations, because variable combinations of environmental changes need to be evoked at each site (Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown Mg/Ca composition and laser ablation profiles are similar between chambers in T. sacculifer (Eggins et al, 2003), so the final chamber is a good approximation for the whole shell chemistry. Additionally, the final chamber of T. sacculifer strongly correlates with SST (Sadekov et al, 2009), and the final chamber represents ~50% of the mass of individuals grown in experimental lab cultures (Lombard et al, 2010). Prior to analysis, individual whole shells were sonicated in deionized water for 20 s and rinsed with methanol.…”
Section: Paleoceanography and Paleoclimatologymentioning
confidence: 99%